Farm Support Payments and Risk Balancing: Implications for Financial Riskiness of Canadian Farms. (24th July 2014) - Uzea, Nicoleta; Poon, Kenneth; Sparling, David; Weersink, Alfons
<x xml:space="preserve">Abstract</x> Risk balancing refers to the balancing of business risk (BR) and financial risk (FR) by firms through their investment and borrowing decisions. Assuming the concept holds, a decrease in income variability (BR) prompts the firm to incur greater debt levels thereby increasing FR. Reducing (BR), which continues to be the central objective of Canadian agricultural policy through programs such as Canadian Agricultural Income Stabilization Program (CAIS)/AgriStability, may lead farmers to take on more FR than they would take otherwise, which, in turn, increases the risk of equity loss. However, it is not known whether Canadian business risk management (BRM) programs offset BR as intended, and whether any potential reduction leads to increased FR (risk balancing) and possibly higher levels of overall risk for individual farm operations. This paper represents the first attempt to shed light on whether Canadian BRM programs fail to reduce farm risk as a result of farmers' risk balancing behavior using a longitudinal farm‐level data set from Ontario. Results are mixed: (1) BRM payments reduce BR for beef farms but not for field crops farms (though the latter result may be due to the lack of data on Crop Insurance payments); (2) risk balancing holds particularly for the larger farms, and (3) BRM programs overall have no significant effect on the likelihood of increased debt use for either sector, on average; however, participation in CAIS/AgriStability increases the probability that farms take on more debt than they would take otherwise for both sectors. Further analysis is needed to determine whether BRM programs increase the probability of default for farms.